Time-Course of Physiologic Variables During Extracorporeal Membrane Oxygenation and Outcome of Severe Acute Respiratory Distress Syndrome. Issue 6 (June 2020) - Spinelli, Elena; Mauri, Tommaso; Carlesso, Eleonora; Crotti, Stefania; Tubiolo, Daniela; Lissoni, Alfredo; Bottino, Nicola; Panigada, Mauro; Tagliabue, Paola; Rossi, Nicola; Scotti, Eleonora; Conigliaro, Federica; et al.
Abstract : In patients undergoing extracorporeal membrane oxygenation (ECMO) for acute respiratory distress syndrome (ARDS), it is unknown which clinical physiologic variables should be monitored to follow the evolution of lung injury and extrapulmonary organ dysfunction and to differentiate patients according to their course. We analyzed the time-course of prospectively collected clinical physiologic variables in 83 consecutive ARDS patients undergoing ECMO at a single referral center. Selected variables—including ventilator settings, respiratory system compliance, intrapulmonary shunt, arterial blood gases, central hemodynamics, and sequential organ failure assessment (SOFA) score—were compared according to outcome at time-points corresponding to 0%, 25%, 50%, 75%, and 100% of the entire ECMO duration and daily during the first 7 days. A logistic regression analysis was performed to identify changes between ECMO start and end that independently predicted hospital mortality. Tidal volume, intrapulmonary shunt, arterial lactate, and SOFA score differentiated survivors and nonsurvivors early during the first 7 days and over the entire ECMO duration. Respiratory system compliance, PaO2 /FiO2 ratio, arterial pH, and mean pulmonary arterial pressure showed distinct temporal course according to outcome over the entire ECMO duration. Lack of improvement of SOFA score independently predicted hospital mortality. In ARDS patients on ECMO, temporal trends of specific physiologic parameters differentiate survivors from non-survivors and could be used to monitor the evolution of lung injury. Progressive worsening of extrapulmonary organ dysfunction is associated with worse outcome. Abstract : Supplemental Digital Content is available in the text.